Focus on prevention: the public is more supportive of “overdose prevention sites” than they are of “safe injection facilities” - Socia, Kelly M. (Criminology & public policy, 2021)
Using a national survey experiment, we examined Americans’ national and local-level support for facilities that provide a safer space for individuals to consume illicit drugs under the supervision of medical professionals. We determined whether support levels differed based on (1) the label used to refer to such facilities (“safe injection facilities” vs. “overdose prevention sites”), (2) whether beneficial information is provided about these facilities regarding either a crime control framework or a public health framework, or not. We also considered how national support differed from local-level support, and how national or local-level perceptions of the opioid epidemic influenced support.